A COMPREHENSIVE STUDY ON IMPACT OF PSYCHOLOGICAL APPROACH TO CANCER TREATMENT - Dr. Abhinav Chauhan; Dr. Rupam; Dr. Praveen yadav; Dr. Shekhar Saini (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
This dissertation investigates the impact of psychological interventions on the quality of life and treatment outcomes for cancer patients, focusing on the fundamental question of how mental health strategies can enhance physical healing and improve coping mechanisms during treatment. Employing a mixed-methods approach, the research incorporates both qualitative and quantitative data, including patient surveys, psychological assessments, and treatment outcome metrics, to evaluate the effectiveness of various psychological strategies such as cognitive-behavioral therapy, mindfulness, and supportive counseling. The findings reveal that patients who engaged in psychological interventions reported significantly improved emotional well-being, reduced levels of anxiety and depression, and enhanced coping mechanisms, which correlated positively with overall treatment outcomes and adherence to medical protocols. These results underscore the critical role of psychological care in oncology, suggesting that integrating mental health support within cancer treatment regimens can lead to holistic improvements in patient health. The significance of these findings extends beyond individual patient care, indicating a need for healthcare systems to adopt a more comprehensive model that incorporates psychological interventions as essential components of cancer treatment. This study has the potential to influence clinical practice by advocating for multidisciplinary approaches that prioritize psychological well-being alongside physical treatment, ultimately fostering better patient outcomes and enhancing the overall quality of cancer care.